Radicalization to violence: a pathway approach to studying extremism - Jensen, Michael (Terrorism and political violence, 2020)
Prior research on extremism has identified a host of psychological, emotional, material, and group-based mechanisms that are potentially important drivers of individual radicalization. However, taken on their own, none of these factors have been shown to lead to extremist behaviors. Instead, radicalization is best understood as a set of complex causal processes in which multiple factors work together to produce extremist outcomes. This paper builds on prior research by showing how radicalization mechanisms drawn from five prominent research traditions combine to form multiple sufficient pathways to extremist violence. We identify these pathways by applying fuzzy-set/Qualitative Comparative Analysis (fs/QCA) to a sample of life-course narratives that includes violent and nonviolent extremists in the United States. We find that both a sense of community victimization and a fundamental shift in individuals’ cognitive frames are present in all pathways and act as necessary conditions for radicalization to violence. These conditions combine with a set of psychological, emotional, group, and material variables to produce eight pathways that are sufficient for explaining violent outcomes. Of these, the pathways that combine psychological rewards and group biases account for the radicalization processes of the majority of the cases in our sample.